2022
DOI: 10.3390/ijms23137121
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Metal-Organic Frameworks as Adjustable Scaffolds in Reticular Chemistry

Abstract: The easy and remote switching of light makes this stimulus an ideal candidate for a large number of applications, among which the preparation of photoresponsive materials stands out. The interest of several scientists in this area in order to achieve improved functionalities has increase parallel to the growth of the structural complexity of these materials. Thus, metal-organic frameworks (MOFs) turned out to be ideal scaffolds for light-responsive ligands. This review is focused on the integration of photores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…From a materials perspective, metal–organic frameworks (MOFs), consisting of metal ions and organic poly complex linkers, have been widely used in gas adsorption/separation, water remediation, drug delivery, energy storage, and conversion because of the large specific surface area, tunable functionalities, homogeneous pore size, and chemical stability. Meanwhile, MOFs have been demonstrated that they can act as precursors or template materials for the fabrication of other desirable novel nanomaterials and porous nanostructured materials. For example, Co-based nanoparticles encapsulated in a hollow N-doped carbon matrix were developed by pyrolysis and an oxidation strategy by using ZIF-67 as a precursor. Benefiting from the synergetic effects of its abundant oxygen vacancies, nitrogen-doped carbon as well as the efficient mass transfer of hollow structures, the optimal samples exhibited high activity toward oxygen reduction and evolution reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a materials perspective, metal–organic frameworks (MOFs), consisting of metal ions and organic poly complex linkers, have been widely used in gas adsorption/separation, water remediation, drug delivery, energy storage, and conversion because of the large specific surface area, tunable functionalities, homogeneous pore size, and chemical stability. Meanwhile, MOFs have been demonstrated that they can act as precursors or template materials for the fabrication of other desirable novel nanomaterials and porous nanostructured materials. For example, Co-based nanoparticles encapsulated in a hollow N-doped carbon matrix were developed by pyrolysis and an oxidation strategy by using ZIF-67 as a precursor. Benefiting from the synergetic effects of its abundant oxygen vacancies, nitrogen-doped carbon as well as the efficient mass transfer of hollow structures, the optimal samples exhibited high activity toward oxygen reduction and evolution reactions .…”
Section: Introductionmentioning
confidence: 99%
“… 29 31 Meanwhile, MOFs have been demonstrated that they can act as precursors or template materials for the fabrication of other desirable novel nanomaterials and porous nanostructured materials. 32 34 For example, Co-based nanoparticles encapsulated in a hollow N-doped carbon matrix were developed by pyrolysis and an oxidation strategy by using ZIF-67 as a precursor. Benefiting from the synergetic effects of its abundant oxygen vacancies, nitrogen-doped carbon as well as the efficient mass transfer of hollow structures, the optimal samples exhibited high activity toward oxygen reduction and evolution reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs) have garnered widespread research attention in many fields, including gas separation, energy storage and conversion, wastewater treatment, catalysis, sensors and others [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The design and synthesis of coordination polymers and MOFs using ferrocene-containing ligands have emerged as a crucial area of research in coordination chemistry [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue is dedicated to exploring various approaches and techniques for the preparation and modification of metal-organic frameworks (MOFs), as well as their applications, with a specific focus on molecular research [1][2][3][4]. Over the past few years, research in this field has continued to evolve and garner significant attention.…”
mentioning
confidence: 99%
“…The review of Saura-Sanmartin A. [4] explores the use of photoresponsive metal-organic frameworks (MOFs) as adjustable scaffolds in reticular chemistry. The easy and remote switching of light makes it an ideal stimulus for a large number of applications, including the preparation of photoresponsive materials.…”
mentioning
confidence: 99%